Students’ motivation to study dentistry in Malaysia: an analysis using confirmatory factor analysis - Che Musa, Muhd Firdaus; Bernabe, Eduardo; Gallagher, Jennifer E. (Biomed Central Ltd., 2015)
Introduction: Malaysia has experienced a significant expansion of dental schools over the past decade. Research into students’ motivation may inform recruitment and retention of the future dental workforce. The objectives of this study were to explore students’ motivation to study dentistry and whether that motivation varied by students’ and school characteristics. Methods: All 530 final-year students in 11 dental schools (6 public and 5 private) in Malaysia were invited to participateat the end of 2013. The self-administered questionnaire, developed at King’s College London, collected informationon students’ motivation to study dentistry and demographic background. Responses on students’ motivation werecollected using five-point ordinal scales. Confirmatoryfactor analysis (CFA) was used to evaluate the underlyingstructure of students’ motivation to study dentistry. Multivariate analysis of variance (MANOVA) was used to compare factor scores for overall motivation and sub-domains by students’ and school characteristics. Results: Three hundred and fifty-six final-year students in eight schools (all public and two private) participated in the survey, representing an 83% response rate for these schools and 67% of all final-year students nationally. The majority of participants were 24 years old (47%), female (70%), Malay (56%) and from middle-income families (41%) and public schools (78%). CFA supported a model with five first-order factors (professional job, healthcare and people, academic, careers advising and family and friends) which were linked to a single second-order factor representing overall students’ motivation. Academic factors and healthcare and people had the highest standardized factor loadings (0.90 and 0.71, respectively), suggesting they were the main motivation to study dentistry. MANOVA showed that students from private schools had higher scores for healthcare and people than those in public schools whereas Malay students had lower scores for family and friends than those from minority ethnic groups. No differences were found by age, sex, family income and school type. Conclusion: Using CFA, this study shows that academic factors were the main motivation to study dentistry in this group of Malaysian students. There were also variations in students’ motivation by students'ethnicity and school sector but not by other factors. Keywords: Motivation, Professional career, Dental students, Malaysian, Dental education